2014
DOI: 10.1542/peds.2013-3106
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive Outcomes in Febrile Infection-Related Epilepsy Syndrome Treated With the Ketogenic Diet

Abstract: Febrile infection-related epilepsy syndrome (FIRES) is a newly recognized epileptic encephalopathy in which previously healthy school-aged children present with prolonged treatment-resistant status epilepticus (SE). Survivors are typically left with pharmacoresistant epilepsy and severe cognitive impairment. Various treatment regimens have been reported, all with limited success. The ketogenic diet (KD) is an alternative treatment of epilepsy and may be an appropriate choice for children with refractory SE. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
59
1
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(69 citation statements)
references
References 17 publications
3
59
1
2
Order By: Relevance
“…Moreover, Lenz and colleagues (2014) have shown that montelukast not only has anticonvulsant effect but also protects against BBB disruption and leukocyte infiltration in a cannula-lesioned cortical area, suggesting that montelukast also decreases neuroinflammation and/or exposure to blood-borne elements [15]. It is well known that areas of focal hyperexcitability can develop in the brain after trauma, infection, ischemia, and excitotoxicity, probably due to neuroinflammation and/or exposure to blood-borne elements [43][44][45][46][47][48][49]. Furthermore, pranlukast treatment protects against global cerebral ischemia in rats and inhibits the expression of NMDA-NR2A receptor [50,51].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, Lenz and colleagues (2014) have shown that montelukast not only has anticonvulsant effect but also protects against BBB disruption and leukocyte infiltration in a cannula-lesioned cortical area, suggesting that montelukast also decreases neuroinflammation and/or exposure to blood-borne elements [15]. It is well known that areas of focal hyperexcitability can develop in the brain after trauma, infection, ischemia, and excitotoxicity, probably due to neuroinflammation and/or exposure to blood-borne elements [43][44][45][46][47][48][49]. Furthermore, pranlukast treatment protects against global cerebral ischemia in rats and inhibits the expression of NMDA-NR2A receptor [50,51].…”
Section: Discussionmentioning
confidence: 99%
“…With the exception of anaesthetic coma, which is not sustainable, and the ketogenic diet in some patients 2, 3 , treatment that effectively controls seizures is lacking in FIRES, and outcomes are generally poor 1 .…”
Section: Introductionmentioning
confidence: 99%
“…Также в литературе встречает-ся описание применения кетогенной диеты наряду с АЭП у 2 пациентов с FIRES как в остром периоде, так и в хроническую фазу сроком от нескольких ме-сяцев до 1 года. Авторы отмечают, что на фоне прово-димой терапии парциальные приступы были редкими, а когнитивные нарушения -легкой степени выражен-ности [14].…”
Section: Ch I Ld Neurology R U S S I a N J O U R N A L O Funclassified